Content Analysis of Evaluations of Public Libraries on Google Maps: The Case of Provincial Public Libraries in Türkiye - Polat, Özgür; Akkaya, Mehmet Ali (Information World, 2023)
As a reflection of the prevalence of the internet world and the attraction it has created all fields of life and almost all disciplines take this medium and what it brings with it much more into consideration. At this point, the first actors that come to mind are social media tools and interactive online applications. The convergence in question undoubtedly encompasses the world of information centers as well. Scientific studies with different qualities and contents not only confirm this convergence, but also draw attention to the speed of change. In this study, it is aimed to draw attention to the importance of the application for libraries by analyzing the evaluations made about the provincial public libraries through the Google Maps application from different perspectives. Thus, the use of the Google Maps application, which is constantly increasing due to the fact that the evaluations and opinions can be freely expressed, especially due to the high level of interaction and satisfaction, and the different associations related to the map, are more referenced by the libraries and the data to be obtained will turn into service adequacy and user satisfaction. aimed to contribute. In the study, besides the written document and document analysis method, the descriptive method was used in the editing of the text. The population of the study consists of 81 provincial public libraries in Türkiye. Within the scope of the research, 6.314 evaluations made about the provincial public libraries over the Google Maps application were analyzed using the MAXQDA program. The findings revealed that the Google Maps application for other information centers in Türkiye, as well as the provincial public libraries, has extremely unique and reference data in terms of increasing service performance, user interaction, social perception, and acceptance. The research, which is the first study in the national literature in which the Google Maps application, which is frequently discussed with a scientific approach in different disciplines, is associated with the field of librarianship. It is considered that it will contribute to its transformation into a “good” library.